Uma Arquitetura para Composição de Serviços com Modelos de Interação Heterogêneos - Huf, Alexis; Siqueira, Frank (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
Current Web-based Services are highly heterogeneous not only on data but also with regard to service interaction. Despite their heterogeneity, composition of these services is required in order to achieve additional functionality. Description languages and composition algorithms for heterogeneous services have been recently proposed. However, existing techniques do not take the Publish/Subscribe paradigm into consideration or do not offer sufficient support for interaction through hypermedia controls as required by the REST architectural style. Analyzing current heterogeneous composition techniques, this dissertation identifies limitations hindering automatic composition of these heterogeneous services. It proposes an architecture and two techniques, adaptiveness and replication, that when combined with a graph-based composition algorithm, enable planning and execution of heterogeneous compositions. In addition to supporting heterogeneity, our prototype achieved similar or better performance than two state-of-the-art homogeneous composition algorithms in most cases.